2005
DOI: 10.1142/s021797920503030x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelastics and Their Properties

Abstract: The effect of a uniform magnetic field on the elastic and viscous properties of new magnetocontrolled materials (magnetoelastics) was studied. It was found that the application of a magnetic field leads to a considerable rise both in Young's modulus and in the viscosity of these materials. We investigated the samples prepared both in the absence of magnetic field and in the magnetic field applied during magnetoelastic curing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The dynamic behavior of polymer systems has been generalized [32] to include terms relevant to these composites, and neutron-spin-echo spectrometry has been used to study magnetic particle behavior within the polymer matrix [33]. The synthesis and performance of anisotropic gels [27,34,35], the effects of matrix material, magnetic filler concentration, and magnetic field strength [2,6] on composite performance have been previously documented. The mode and mechanism of deformation [2] as well as the saturation [36] and hysteretictype deformation ratio [37] behavior have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic behavior of polymer systems has been generalized [32] to include terms relevant to these composites, and neutron-spin-echo spectrometry has been used to study magnetic particle behavior within the polymer matrix [33]. The synthesis and performance of anisotropic gels [27,34,35], the effects of matrix material, magnetic filler concentration, and magnetic field strength [2,6] on composite performance have been previously documented. The mode and mechanism of deformation [2] as well as the saturation [36] and hysteretictype deformation ratio [37] behavior have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Several MR elastomers have been fabricated by dispersing iron particles in viscous liquids, degassing the mixture and making it cured in a mold [3][4][5][6][7][8][9][10][11][12][13][14]. The experimental study has been performed on the static properties and dynamic behaviors of MR elastomers and their dependence on ingredient volume fraction, external magnetic field strength, vibration frequency and motion magnitude [4,7,8,[15][16][17][18]. MR elastomers were mostly considered to work in shear deformation, and were generally regarded as linearly viscoelastic materials so that the dynamic behavior of MR elastomers can be described by using the complex modulus dependent on vibration frequency and controllable by external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…This combination can produce several kinds of movements, including flexion and extension, abduction and adduction, rotation etc. A comparison of force and strain capabilities for Magpol and other artificial muscle materials is shown in Figure 11, 78, 89, 90, 98, 105, 106. It is found that Magpol has actuation properties closest to those of natural muscles.…”
Section: An Example Of Magpol Actuators: Artificial Muscle Materialsmentioning
confidence: 95%
“… Stress and strain characteristics of practical artificial muscle materials 11, 78, 89, 90, 98, 105, 106…”
Section: An Example Of Magpol Actuators: Artificial Muscle Materialsmentioning
confidence: 99%